Return to work of cancer survivors: a prospective cohort study into the quality of rehabilitation by occupational physicians. Issue 5 (1st May 2003) - Verbeek, J; Spelten, E; Kammeijer, M; Sprangers, M
Abstract : Aims: To describe and assess the quality of rehabilitation of cancer survivors by occupational physicians and to relate the quality of the process of occupational rehabilitation to the outcome of return to work. Methods: One hundred occupational physicians of a cohort of cancer survivors were interviewed about return to work management. Quality of rehabilitation was assessed by means of four indicators that related to performance in knowledge of cancer and treatment, continuity of care, patients complaints, and relations at work. The cohort of patients was prospectively followed for 12 months to assess time to return to work and rate of return to work. Patients' and physicians' satisfaction with care was also assessed. The relation between performance and these outcome measures was studied in a multivariate analysis, taking into account the influence of other work and disease related factors that could potentially predict return to work. Results: For knowledge of cancer and treatment, only 3% had optimal performance because occupational physicians did not communicate with treating physicians. For continuity of care, patient complaints, and relations at work, performance was optimal for 55%, 78%, and 60% of the physicians respectively. After adjustment for other prognostic factors, overall physician's performance (hazard ratio (HR) 0.5, 95% CI 0.3 to 0.8) and continuity of care (HR 0.5, 95% CI 0.3 to 0.9) were related to the return to work of patients. Overall optimal performance was also related to a small but significant higher level of satisfaction with care, both for patients and physicians. Conclusion: Quality of occupational rehabilitation of cancer survivors can be improved substantially, especially with regard to communication between physicians and continuity of care. There is a need for the development of more effective rehabilitation procedures which should be evaluated in a randomised controlled trial.